ANALYSIS OF SOCIAL COMPETENCE OF AN EDUCATOR IN IMPROVING EXCELLENCE AVIATION VOCATIONAL CADETS - Dhian Supardam; Hadi Prayitno; Musri Kona; Nining Idyaningsih (GoAcademica Research dan Publishing, 2023)
It is important that educators who are responsible for education at these institutions are required to carry out education correctly and accurately in accordance with the vision and mission of the institution. The purpose of this research, of course, is to build the excellence of aviation cadets at the Aviation Polytechnic. This research approach is qualitative. This type of research is a case study, which is research conducted on a subject that has its own characteristics. The method used in this research to collect data there are three techniques, namely participant observation, in-depth interviews, and study of documents. So that the results of social competence show that caregivers and teaching staff at the Surabaya Polytechnic have good social competence as seen from good cooperation in fostering cadets, educators also participate in fostering cadets, and there is a sensitivity of educators to the individual development of cadets.